Uncoupling convention : psychoanalytic approaches to same-sex couples and families - D'Ercole, Ann; Drescher, Jack, 1951- (Bending psychoanalysis book series., 2004)
What does it mean to be member of a gay/lesbian couple or family? The contributors to Uncoupling Convention: Psychoanalytic Approaches to Same-Sex Couples and Families address this question by drawing on two cultural movements of the twentieth century: psychoanalysis and the gay/lesbian civil rights movement. Taken together, these traditions provide a framework for understanding, and providing psychotherapeutic assistance to, gay and lesbian patients who present with troubled relationships. The contributors to this volume espouse a clinical focus that supplants the heterosexual.